2016
DOI: 10.22502/jlmc.v4i2.95
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Carcinoma Prostate in Transurethral Resection Specimen in a Teaching Hospital of Nepal

Abstract: Introduction: As suggested through several autopsy studies there is a high prevalence of latent prostate  cancer in the population. A much smaller proportion of prostate  cancer is detected because of clinical symptoms. This study was done to identify the rates of incidentally detected prostate cancer in patients undergoing surgical management of Benign Prostatic Hyperplasia (BPH) in our centre.   Methods: A retrospective review was done on all transurethral resections of the prostate (TURP)  cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
6
2
0
Order By: Relevance
“…Thapa N et al and Begum Z et al also evaluated only TURP specimens in their respective studies. 12,13 Thapa N et al in their study found 92.2% cases were of BPH, 4.8% were prostatic cancers and these observations were comparable with our findings. 12 Begum Z et al also observed almost similar percentage of BPH and adenocarcinoma cases constituting 96% and 4% respectively.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Thapa N et al and Begum Z et al also evaluated only TURP specimens in their respective studies. 12,13 Thapa N et al in their study found 92.2% cases were of BPH, 4.8% were prostatic cancers and these observations were comparable with our findings. 12 Begum Z et al also observed almost similar percentage of BPH and adenocarcinoma cases constituting 96% and 4% respectively.…”
Section: Discussionsupporting
confidence: 93%
“…12,13 Thapa N et al in their study found 92.2% cases were of BPH, 4.8% were prostatic cancers and these observations were comparable with our findings. 12 Begum Z et al also observed almost similar percentage of BPH and adenocarcinoma cases constituting 96% and 4% respectively. 13 The age of the patients in our study ranged from 39 years to 92 years.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations